2019
DOI: 10.1136/neurintsurg-2019-015019
|View full text |Cite
|
Sign up to set email alerts
|

National trends in endovascular therapy for acute ischemic stroke: utilization and outcomes

Abstract: ObjectiveFollowing widespread acceptance of endovascular therapy (ET) for large vessel occlusion stroke in 2015, we assessed nationwide utilization of revascularization for acute ischemic stroke (AIS).MethodsWe utilized the 2013–2016 Healthcare Cost and Utilization Project Nationwide Readmissions Database. We identified AIS admissions, treatment with intravenous thrombolysis (IVT), ET, and vascular risk factors using International Classification of Disease Clinical Modification codes. Main predictor of outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
1
19
1
Order By: Relevance
“…With the introduction of more effective treatment methods such as these, the number of patients with an expected favorable outcome may have increased regardless of the hospital they visited. The rate of a good outcome in this study was higher than a study using other insurance claims data but was slightly lower when compared to the ratio of patients with modified Rankin scale (mRS) 0-2 at three months (7,8,24). In this study, some patients who were not discharged home may have received treatments in a rehabilitation hospital and then recovered to mRS 0-2 at three months.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…With the introduction of more effective treatment methods such as these, the number of patients with an expected favorable outcome may have increased regardless of the hospital they visited. The rate of a good outcome in this study was higher than a study using other insurance claims data but was slightly lower when compared to the ratio of patients with modified Rankin scale (mRS) 0-2 at three months (7,8,24). In this study, some patients who were not discharged home may have received treatments in a rehabilitation hospital and then recovered to mRS 0-2 at three months.…”
Section: Discussioncontrasting
confidence: 78%
“…Therefore, an increase in the number of hospitals performing this procedure will likely result in an increased number of patients with a favorable prognosis. Indeed, previous studies reported improved prognoses in real-world clinical settings after the recent guideline changes (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with other studies, 3,4 our analysis of the nationwide data showed that the patients treated with ET had better outcomes in the MT period than in the non-advanced MT period. Over time, the baseline prognostic characteristics, reflected by age and comorbidities, got worse; however, the outcomes of the patients generally improved; this was supported by the annual trend analyses (Supplementary Table 2).…”
supporting
confidence: 92%
“…The corresponding guidelines were revised in 2019 to broaden the scope of MT within 24 hours of symptom onset [ 2 ]. In previous studies, MT have improved the prognoses of patients in real-world clinical settings [ 3 , 4 ]. Using nationwide representative data, this study aimed to evaluate the national trends in clinical outcomes of patients treated with endovascular therapy (ET) in South Korea.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11] Despite the proven efficacy of these treatments, IV tPA and MT remain severely underutilized. 12,13 To increase utilization of these therapies and standardize AIS care across the US, primary and comprehensive stroke centers (CSCs) were established as system-based strategies to improve outcomes. The first CSC certifications approved in 2012 required, among other things, high volumes, advanced imaging techniques, dedicated neurological intensive care units, and after-hospital care coordination for patients.…”
mentioning
confidence: 99%